1999
DOI: 10.1080/105504999306045
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental History and Substance Use Severity in Drug Treatment Patients

Abstract: The authors explored the relationship between the history of parental problematic alcohol and drug use and their adult children's alcohol and drug use disorders. Subjects were 347 admissions to an outpatient substance abuse program. There was a positive relationship between the number of parents affected by alcohol and/or drug problems and the percentage of probands with co-existing alcohol and drug use disorders for probands with alcohol use disorders but not for those with only drug abuse. Probands with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…In line with other research, alcohol problems were the most frequently reported problem among family members and were uniformly high, ranging from 42% among grandparents to 66% among parents (Boyd et al, 1999; Powell et al, 1982; Rounsaville et al, 1991). In the drug and psychiatric problem domains, rates of family history increased by generation, with younger family members (i.e., siblings) showing the highest rates of these problems.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with other research, alcohol problems were the most frequently reported problem among family members and were uniformly high, ranging from 42% among grandparents to 66% among parents (Boyd et al, 1999; Powell et al, 1982; Rounsaville et al, 1991). In the drug and psychiatric problem domains, rates of family history increased by generation, with younger family members (i.e., siblings) showing the highest rates of these problems.…”
Section: Discussionsupporting
confidence: 85%
“…Family history of substance abuse is an important correlate of problem severity in primary substance abusers (Kendler et al, 2008; Coviello et al, 2004; Pickens et al, 2001; Merikangas et al, 1998; Bierut et al, 1998; Boyd et al, 1999; Rutherford, Metzger & Alterman, 1994). Positive family history is associated with increased severity of substance use disorders as well as a range of family, social, and psychological problems (Boyd et al, 1999; Coviello et al, 2004; Pickens et al, 2001; Rutherford et al., 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Across different developmental periods, parental substance use and emotional distress have been found to have a negative influence on parenting practices, family functioning, and child adjustment (Boyd et al 1999; Johnson and Leff 1999). For HIV infected parents, alcohol and illicit drug use represent a significant problem (Coyle 1998; Goldstein et al 2005) with 76% of HIV infected mothers reporting at least one drug use (Lee, Lester, and Rotheram-Borus 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic risk factors appear to contribute to the manifestation of substance use disorders. In several studies, a family history of substance use was an important predictor of disease onset and disease severity in substance abusers without comorbid psychiatric diagnoses (Bierut et al, 1998; Boyd et al, 1999; Coviello et al, 2004; Kendler et al, 2008; Merikangas et al, 1998). …”
Section: Introductionmentioning
confidence: 99%